Issues on Islamic banks’ Nostro accounts - Syed Alwi, Sharifah Faigah; Ibrahim, Uzaimah; Sawari, Mohd Fuad (Universiti Teknologi MARA, 2013)
All Islamic banks in Malaysia which involve with the international trade transaction will have to have a Nostro accounts with a conventional correspondent/agent banks in order to make payments through them. The objective of this study is to clarify the issue on the usage of Nostro accounts in conventional banks by the Islamic banks where these accounts deal with riba (interest) in their daily transactions from the Shariah perspective. This study adopts the qualitative method as the main research methodology. The information on the involvement of 12 Islamic banks in Malaysia with Nostro accounts in conventional banks is gained from semi-structured interviews conducted with bankers who directly involved with international trade payments. As a result, this study discovered two main issues. First is the issue on the permissibility of the involvement of the Islamic banks with the Nostro accounts. While the second issue is the tendency of some Islamic banks leverage on the conventional parents’ banks Nostro accounts. This study analyzes these issues by determining whether they are in line with Shariah principles.